Praktik Metaverse dalam Pendidikan Agama Kristen - Leonardi Daniel Herlim (Sekolah Tinggi Agama Kristen Samarinda, 2023)
Abstract: Metaverse is a technology that is develop from the internet. Within the metaverse you can communicate, shop, work, go to school, worship, travel, watch concerts, play games and many other things. Metaverse is in the public spotlight because in metaverse you can state or represent yourself in the form of an avatar so that you can be directly involved in every activity in it. The problem is if this technological progress is not accompanied by healthy spiritual growth or spirituality, it can lead to ethical, moral, social violations in the use of such technology, especially in its use in the field of education. In this paper, we will analyse the impact of metaverse in the world of Christian religious education on students, especially those closely related to presenting God in cyberspace. The study was conducted using the literature study method by analysing papers, journals, from various domestic and foreign institutions. The results of the study show that metaverse can be used as a means of supporting Christian religious education as long as the spiritual growth level of students is maintained and metaverse is only used in certain subjects or courses, especially those that require simulation. Abstrak: Metaverse adalah suatu teknologi yang merupakan pengembangan dari internet. Di dalam metaverse anda dapat berkomunikasi, berbelanja, bekerja, bersekolah, beribadah, berpergian, menonton konser, bermain game dan masih banyak hal lain lagi yang dapat dilakukan. Metaverse menjadi sorotan masyarakat karena di dalam metaverse anda dapat menyatakan atau merepresentasikan diri anda dalam wujud avatar sehingga anda dapat langsung terlibat dalam setiap aktivitas anda di dalamnya. Yang menjadi masalah jika kemajuan teknologi ini tidak disertai dengan pertumbuhan rohani atau spiritualitas yang sehat. Akibatnya dapat menyebabkan terjadinya pelanggaran-pelanggaran etika, moral, sosial dalam penggunaan teknologi tersebut khususnya dalam penggunaannya di bidang pendidikan. Dalam makalah ini akan dianalisa bagaimana dampak metaverse dalam dunia pendidikan agama Kristen terhadap anak didik khususnya yang berkaitan erat dengan menghadirkan Allah di dunia maya. Kajian yang dilakukan menggunakan metode studi kepustakaan dengan menganalisis makalah, jurnal dari berbagai institusi dalam dan luar negeri. Hasil kajian menunjukkan bahwa metaverse dapat digunakan sebagai sarana penunjang pendidikan agama Kristen selama tingkat pertumbuhan kerohanian dari anak didik terjaga dan metaverse hanya digunakan pada mata pelajaran atau mata kuliah tertentu khususnya yang memerlukan simulasi.